Farmers’ preference for agricultural radio programmes in Niono area of Segou, Mali (2019)
This study examined farmers’ preference for agricultural radio programmes in Niono area of Segou, Mali. Dataon farmers’ radio set ownership, listening time and listenership of agricultural radio programmes were obtained from 205 randomly selected respondents. Data were analysed using descriptive (percentages) and inferential statistics (Chi-square and Pearson’s Product Moment Correlation) at α=0.05. Most farmers had high radio set ownership (79%), preferred listening to radio in the evening (61.50%) but had low listenership status (60.5%). The respondents preferred listening to Cikelaw ka Kene from Kaira radio station (x̅ =1.2683). Farmers’ radio set ownership (X2 = 39.623), listening preferred time (r = 0.22) and their listenership status (r = 0.696) were significantly related to farmers’ radio agricultural programme preference. Broadcast of Cikelaw ka Kene from Kaira radio station should be sustained, while relevant agricultural information should be targeted at the evening period to enhance listenership among farmers in the study area.